A Review Of Diaphragm Wall Construction-White Swan Hotel ? Synopsis - Q. M. Huang (Deep Foundations Institute, 2010)
In 1979 our company undertook the project of infra-structural work of White Swan Lake Hotel, (International class ) Guangzhou. Visit to the site showed that it was situated at the riverside, covering an area of 54,000 M2 with 30,000 M2 of which reclaimed from Pearl River. The material used for reclamation was black sand which was dredged from the nearby riverbed. The sand had the properties of high permeability and very low internal friction. The basement of the building was 6.2 m below ground level and 3 m lower than the riverbed. Apart from the pile foundation, a diaphragm wall was to be constructed prior to the commencement of excavation work for basement. A feasibility study was carried out to determine the method of construction which would maximize utilization of the plants and equipment that were available in the execution of the aforesaid foundation works. This report concerns only the construction of the diaphragm wall and the performance of the plants employed. A detailed delineation of the construction method is herein discussed